PENGARUH PROFITABILITAS, UKURAN KANTOR AKUNTAN PUBLIK, KOMITE AUDIT TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Ni Wayan Eta Pristya Devi; Ni Wayan Alit Erlina Wati (UNHI Press, 2021)
Audit Delay is the time for completion of the audit by the auditor as seen from the time difference between the financial statements and the date of the financial report audit opinion. In this research, it is tested how the effect of profitability, KAP( Public accounting firm), Audit Committee on Audit Delay. This research was conducted at the Consumer Goods Industrial Sector Manufacturing companies.listed on the.Indonesia Stock.Exchange for the period 2015-2019. The sample was determined using.purposive.sampling method, with a total sample of 61 companies. This research uses descriptive analysis test, classic assumption test, multiple linear regression test to test the hypothesis of this study.